2016
DOI: 10.1002/bmc.3761
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of Caulis Sinomenii bioactive ingredients with dual‐target NF‐κB inhibition and β2‐AR agonizing activities

Abstract: Caulis Sinomenii (CS) is a valuable traditional medicine in China. Its extract can act as an anti-inflammatory agent and a vascular smooth muscle relaxant. However, the underlying mechanisms remain unknown. In this study, we developed a simple dual-target method based on ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry combined with a dual-target bioactive screening assay for anti-inflammatory and antispasmodic activities to characterize the chemical structure of various bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Other findings confirmed that the Sinomenii caulis extract, in which MGN is found, significantly reduced the NF-κB expression [55]. More specific, the MGN isolated from Sinomenii caulis presented significant inhibitory effect on NF-κB and inflammatory cytokines, including IL-6 and IL-8, whose transcription is affected by NF-κB [94].…”
Section: Anti-inflammatory Immunomodulatory and Anti-allergic Effectssupporting
confidence: 56%
See 1 more Smart Citation
“…Other findings confirmed that the Sinomenii caulis extract, in which MGN is found, significantly reduced the NF-κB expression [55]. More specific, the MGN isolated from Sinomenii caulis presented significant inhibitory effect on NF-κB and inflammatory cytokines, including IL-6 and IL-8, whose transcription is affected by NF-κB [94].…”
Section: Anti-inflammatory Immunomodulatory and Anti-allergic Effectssupporting
confidence: 56%
“…The results showed that expression of proteins-phosphorylated p38, ERK, and JNK were lower after MGN treatment in a dose-dependent manner [90,93] contradicting previous findings. Additionally, MGN exhibited no cytotoxicity effect on RAW264.7 cells [94]. Other findings confirmed that the Sinomenii caulis extract, in which MGN is found, significantly reduced the NF-κB expression [55].…”
Section: Anti-inflammatory Immunomodulatory and Anti-allergic Effectsmentioning
confidence: 57%
“…The crude P. koraiensis bark extract was prepared in 95% ethanol 1:7 (w/v, 5 kg/35 L), concentrated by using Rotary evaporator to dryness (328.37 g), obtained extract was uniformly dispersed in water to get aqueous suspension and partitioned with organic solvents follow the sequence: Petroleum ether extract (PEE), dichloromethane extract (DME), ethyl acetate extract (EAE), n-butanol extract (NBE). [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Magnoflorine is practically insoluble in water and a very weak acidic compound. Magnoflorine is an inhibitor of nuclear factor kappa B activation and to be an agonist at the β2-adrenergic receptor [10].…”
Section: Discussionmentioning
confidence: 99%